2007
DOI: 10.1128/jb.00166-07
|View full text |Cite
|
Sign up to set email alerts
|

Enzymology and Evolution of the Pyruvate Pathway to 2-Oxobutyrate in Methanocaldococcus jannaschii

Abstract: The archaeon Methanocaldococcus jannaschii uses three different 2-oxoacid elongation pathways, which extend the chain length of precursors in leucine, isoleucine, and coenzyme B biosyntheses. In each of these pathways an aconitase-type hydrolyase catalyzes an hydroxyacid isomerization reaction. The genome sequence of M. jannaschii encodes two homologs of each large and small subunit that forms the hydrolyase, but the genes are not cotranscribed. The genes are more similar to each other than to previously chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 45 publications
1
80
0
Order By: Relevance
“…If this reaction was drastically inhibited, the energy yield and the processes of the entire TCA cycle as well as the glyoxylate and GABA shunts would have all been significantly affected. Interestingly, some studies confirmed that LeuB (3-isopropylmalate dehydrogenase) is a broad-specificity enzyme that can catalyze the oxidative decarboxylation of 3-methylmalate, as well as D-and L-malate in addition to its cognate substrate 3-isopropylmalate (64,65). Moreover, the ilvEBHC-leuABCD operon was remarkably up-regulated at 13 h at the transcriptional level (Fig.…”
Section: Fig 2 Cog Analysismentioning
confidence: 71%
“…If this reaction was drastically inhibited, the energy yield and the processes of the entire TCA cycle as well as the glyoxylate and GABA shunts would have all been significantly affected. Interestingly, some studies confirmed that LeuB (3-isopropylmalate dehydrogenase) is a broad-specificity enzyme that can catalyze the oxidative decarboxylation of 3-methylmalate, as well as D-and L-malate in addition to its cognate substrate 3-isopropylmalate (64,65). Moreover, the ilvEBHC-leuABCD operon was remarkably up-regulated at 13 h at the transcriptional level (Fig.…”
Section: Fig 2 Cog Analysismentioning
confidence: 71%
“…Grown aerobically at 37°C in Luria-Bertani Miller medium supplemented with ampicillin (100 g ml Ϫ1 ), these cultures were induced in mid-logarithmic-growth phase with 0.1% D-lactose. Cells were harvested and lysed as described previously, and the MMP0704 proteins were purified by nickel affinity chromatography using standard methods (13). Fractions containing the MMP0704-His 6 protein were combined in dialysis tubing (SpectraPor4; 14,000-molecular-weight cutoff) and dialyzed for 15 h in 2 liters of buffer containing 50 mM KCl and 20 mM Tris-HCl (pH 8.0) at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Dialysis was continued for 5 h in fresh buffer before the protein inside the dialysis tubing was concentrated by dehydration with 20,000-Da polyethylene glycol. The MJ0283 proteins were purified by heat treatment of cell extracts prepared in a mixture of 50 mM KCl and 20 mM Tris-HCl (pH 8.0) (13). Total protein concentrations were determined by the Bradford dye-binding method (Thermo-Pierce) using bovine serum albumin as a standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative pathway from pyruvate (the citramalate pathway) requires fewer ATP equivalents and likely was the ancestral pathway. This pathway, first described in Leptospira (10) as a seemingly anomalous variation, is increasingly becoming recognized as either the favored route or the sole route to isoleucine biosynthesis in nature (23). Many organisms have the potential to utilize either pathway, with the citramalate pathway likely being the preferential route.…”
Section: Branches Of the Ask Networkmentioning
confidence: 99%